Adicionando ao middleware EXEHDA o suporte a aplicações orientadas a atividades humanas cotidianas - Ferreira, Giuliano Geraldo Lopes (2010)
Currently, Pervasive Computing is focused on the development of programmable and interactive environments, which are intended to help the user in daily activities. The health system of the future envisages the use of Pervasive Computing as a way of optimizing and automating clinical activities. Under such perspective, the present study has tried to add, in a middleware for pervasive environment management, the supporting for management and accomplishment of clinical tasks (pervasive applications that help physicians perform their activities), fulfilling some requirements of activities-oriented computing, and creating a tool that will help physicians in their daily tasks. In modeling of the tasks management system, the middleware EXEHDA Execution Environment for Highly Distributed Applications has been used to manage the pervasive environment where tasks will be performed. Due to the flexible features of EXEHDA, as the integration of new services, the supporting of the middleware to the new tasks management was added as a new subsystem, composed by the services that implement the new features. So, the main contribution of present study was the modeling of the architecture for the new subsystem of EXEHDA, responsible for management of tasks in pervasive environment. As a secondary contribution, was developed a prototype of the core of this new subsystem (a service for managing tasks), already providing same integration within other services modeled for the architecture. This prototype can be used, during the course of the ClinicSpaces Project, as a basis for testing and evaluation of other services and to facilitate the participation of professionals from other areas in the project.